ONLINE SELLING REGISTERS IN FACEBOOK GROUP SELLING AND BUYING ANYTHING AND THE IMPLEMENTATION OF THE LEARNING OF INDONESIAN LANGUAGE IN SMA - Ediwarman, Ediwarman; Syafrizal, Syafrizal; Pahamzah, John (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this study is to describe the form of abreviation and function of the register language in the Facebook group